Knowledge and Attitude of Dentists Regarding Patients Undergoing Bisphosphonate Treatment: a Comparative Questionnaire - Albu-Stan, Ioana-Aurița; Petrovan, Cecilia; Cerghizan, Diana; Eremie, Lia Yero; Crăciun, Adriana Elena; Copotoiu, Constantin (Journal of Interdisciplinary Medicine, 2018)
Osteonecrosis of the jaw is an uncommon but serious complication related to oral and intravenous bisphosphonate (BP) therapy. Its pathogenesis is not well understood, and there are no universal protocols accepted to treat it. The of our study was to use the same questionnaire as four years ago to evaluate the awareness of dentists in Tîrgu Mureș regarding the dental treatments that can be applied in patients on BP therapy, and to assess how their knowledge on the subject has evolved over these years. We used the same questionnaire-based study as four years ago among dentists in Tîrgu Mureș, raising important issues such as: is the patient asked about current or previous treatments with BPs, do they perform surgical treatment in these patients, do they know under what conditions they can perform this treatment, or do they deem it necessary to contact the prescriber before surgical treatment. One-hundred twenty questionnaires were returned. The majority of respondents (n = 113, 94.2%) included the question regarding the use of BPs in their medical records. Of all respondents, 48 (40%) perform dental or surgical treatments on patients undergoing BP therapy, 68 (56.7%) do not perform dental or surgical treatments on these patients, and four of the respondents (3.3%) did not know the answer. One hundred (83.3%) respondents always contact the prescriber prior to surgery in these patients, regardless of how BPs are administered. According to the findings of the present study, many of the respondent doctors have heard about BPs and their complications, but they are not aware of the fundamental concepts of bisphosphonate-related osteonecrosis of the jaw prevention and treatment protocols. In the absence of appropriate protocols, the quality of life of these patients is compromised.